Experimental Investigations on the Influence of Flux Control Loop in a Direct Torque Control Drive. - Bhoopendra Singh; Shailendra Jain; Sanjeet Dwivedi (Institute of Advanced Engineering and Science, 2012)
Accurate flux estimation and control of stator flux by the flux control loop is the determining factor in effective implementation of DTC algorithm. In this paper a comparison of voltage model based flux estimation techniques for flux response improvement is carried out. The effectiveness of these methods is judged on the basis of Root Mean Square Flux Error (RMSFE) and Total Harmonic Distortion (THD) of stator current. The theoretical aspects of these methods are discussed and a comparative analysis is provided with emphasis on digital signal processor (DSP) based controller implementation. Further the effect of operating flux on the performance of induction motor drive in terms of dynamic response, torque ripple and efficiency of operation is carried out. The proposed investigation is experimentally validated on a test drive.DOI: http://dx.doi.org/10.11591/ijpeds.v2i4.554